Analysis of the Application of the HIRARC Method (Hazard Identification Risk Assessment and Risk Control) and HAZOPS (Hazard and Operability Study) in Identifying Potential Hazards and Risks in the Assembling Contractor Company Division - Farida Pulansari; Isna Nugraha (Future Science, 2023)
Contractor company is a company in Indonesia that produces various kinds of industrial component needs. In the manufacture of these various products, the contractor company has several main processes, one of which is assembly. In addition, a company must have experienced a work accident, so the role of K3 is very important to ensure the safety and health of employees in carrying out their work. Therefore, the contractor company conducts an analysis using two methods, namely the HIRARC method and the HAZOP method. By using these two methods, it aims to determine the potential hazards and risks in the assembly section. Based on the research on the level of hazard through the parameters of likelihood and severity, it is obtained a risk rating consisting of 4 levels, namely Low, Moderate, High, and Extreme. Meanwhile, in determining the accident category, there are 4 categories, namely low risk, medium risk, high risk, and extreme risk.